Peran Emosi Dalam Interpretasi Musikal Musisi Untuk Meningkatkan Kinerja Estetis (Studi Kasus: Komparasi Pada Pemain Cello dan Gitar) - Nathan Thomas (Universitas Negeri Surabaya, 2022)
The complex task in musical performance, sometimes makes musicians get an unsatisfactory evaluation. On the other hand, the structural approach to music itself which is believed to be a fundamental tool for musical interpretation has not clear yet how its capacities could become the basis for translating written notes into musical sounds. On the other hand, music is experienced not exclusively as a mere structure and sound event but also experienced as subjective events. This study, therefore, explores the role of musician's subjective experiences, particularly emotions, in shaping musical interpretations. This study uses a qualitative method with a comparative approach. This approach is used to investigates how emotions can mediate the transformation of written notes into musical sounds. A comparison of two cases of interpretation on the cellist and on the guitar player is held in order to explain if there are differences in the interpretation process of the two groups of musicians. The result of this study shows that: (1) Emotional experience gained in the socialization of everyday emotions plays an important role in understanding music (2) After musicians can apprehend the emotions contained in the musical structure, they can manifest them into an acoustic code that has an iconic relationship with the emotional content of the musical structure (3) Emotional experience posits as the basis for translating structural information into meaningful sound.